Children's Encyclopedia of British History - Bahn, Paul (Kingfisher Publications Plc, 1996)
This book tells the fascinating story of the British -from the earliest Stone Age cave dwellers and Roman settlers right up to the end of the Millennium.
Keywords: Juvenile literature- Non-Fiction